Karakter Kepemimpinan Ideal dalam Organisasi, Study Case : Project Management Telkom Regional 3 Jawa Barat - Aziz, Tradiga Nur Aziz; Hermanto, Bambang; Wulan Tresna, Pratami (Program Studi Manajemen FEBM UMRAH, 2022)
PT. Telkom Indonesia, which is an industry providing complete communication network services. PT. Telkom Indonesia claims that it is currently one of the industries that provide the most telecommunications and information services. The research procedure used is a descriptive analysis procedure, which is a method of universally describing the facts found by the library research method and field research to be precise at PT. Telekomunikasi Indonesia Project Management Division T-Reg 3 West Java, This matter exists because of management activities, which include planning (planning), directing (leading), organizing (organizing), and controlling (controlling). The leader in the Autocratic type according to the Project Manager of Telkom Regional 3 West Java with a very large rating is 9 with a rating score and a weight of 1.71. This type of Charismatic Leadership is given a Rating by the Project Manager of Telkom Regional 3 West Java by giving a fairly large rating is 8 with a rating score and a weight of 1.44.